Polish Evangelical Churches Contribution to Building a Civil Society - Karolina Czech (Forum Pedagogiczne, 2016)
The article contains considerations concerning a role of Churches and religion in building the civil society, bringing the readers closer to the specific movement in the history of Christianity which is evangelicalism and to Churches and communities that have grown out of this movement. The author concentrates mainly on Poland, pointing out that for Poles faith and Church membership is still a very important thing. In the article there are presented two examples of evangelical Churches, i.e., the Pentecostal Church in Poland and the Baptist Church in Poland; their interest in the common good and social engagement as well as their effort put into educating children to be responsible citizens has been underlined.